Students’ Perceptions of Using Digital Product in English Class Activities at SMAN 3 Pekanbaru - chairunisa suci; destina kasriyati (ELT-Lectura, 2021)
Digital products is a learning media, when learning at home become one of choice learning now. The aim of this study at investigiting students' perceptions of using digital products in learning at SMAN3 Pekanbaru. This study was a survey research conducted from March to April 2021 in grade 11. The questionnaire was used as the main instrument for collecting data. Data analysis was performed by categorizing student responses to each questionnaire question into graphs. The data was analyzed based on the responded "strongly agree", "agree", "neutral", "disagree", and "strongly disagree." After that, the number of students who gave responses was converted into percent units and entered into a graph. The findings in research show that the students' perceptions of using digital products in terms of "Convenience" are at the highest level with a total of 37.3% followed by "Academic reason" 34.4%, "Teaching and Learning Benefit" 31.8%, "Social Networking" 30.5%, " E-learning Perceptions "30.1%," Social Influence "27.9%," Ease of Use "27.9%, and" Bariers "13.9%. In conclusion, the use of digital products for learning resources can facilitate students in the learning process.